Accumulation Mechanism of Marine Shale Gas Reservoir in Anticlines: A Case Study of the Southern Sichuan Basin and Xiuwu Basin in the Yangtze Region. (7th March 2019) - Zhang, Kun; Song, Yan; Jiang, Shu; Jiang, Zhenxue; Jia, Chengzao; Huang, Yizhou; Wen, Ming; Liu, Weiwei; Wang, Pengfei; Li, Xin; Liu, Tianlin; Xie, Xuelian; et al.
Abstract : The study of tectonics is one of the important aspects of shale gas preservation. It is vital for understanding how to determine the enrichment regularity of marine shale gas in anticlines. This paper focuses on typical shale blocks in the southern Sichuan Basin and shale in the Upper Ordovician and the Lower Silurian. In this study, triaxial unloading tests, permeability tests perpendicular and parallel to the stratification plane, FIB-HIM tests, and inclusion analyses are carried out with real drilling data. The enrichment regularity of marine shale gas in anticlines is studied by considering 2 aspects: the angle of the limbs and the burial depth. For anticlines with adjacent synclines, the migration regularity of shale gas is considered by 3 aspects: the dynamics, channels, and processes of migration. This study reveals that a limb angle greater than 120° reflects relatively good conditions for shale gas preservation, while limb angles lesser than 70° indicate relatively poor conditions. This study also suggests that during the process of uplift, large-scale concentrated fractures will form at a certain depth range and horizontal stress field, resulting in the large loss of shale gas. The regression equation of the fractured depth (H ) and the horizontal stress (S ) is presented asH = 15.404 S − 754.41 (with a correlation coefficientR 2 = 0.6834 ). The stratification plane and the organic pores form the migration channel of natural gas that is horizontal to the stratification plane in shale. Under the condition of both anticlines and contiguous synclines, shale gas escapes through fractures resulting from extrusion along the anticline and the uplift effect. In addition, driven by differences in the formation pressure coefficients, shale gas is capable of migrating in a short-distance stair-type style from synclines to the adjacent anticlines. Thus, if the drilling costs allow, the well locations should be placed in the more deeply buried synclines.